Physical Therapy Interventions for the Management of Biceps Tendinopathy: An International Delphi Study - Amy W. McDevitt; Joshua A. Cleland; Simone Addison; Leah Calderon; Suzanne Snodgrass (International Journal of Sports Physical Therapy)
# Background